2014
DOI: 10.2174/1381612820666140905123529
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Antimicrobial Drug Delivery to Biofilm

Abstract: Biofilms are formed by the attachment of single or mixed microbial communities to a variety of biological and/or synthetic surfaces. Biofilm micro-organisms benefit from many advantages of the polymicrobial environment including increased resistance against antimicrobials and protection against the host organism's defence mechanisms. These benefits stem from a number of structural and physiological differences between planktonic and biofilm-resident microbes, but two main factors are the presence of extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 0 publications
1
58
0
Order By: Relevance
“…Recent studies have shown that many diseases associated with bacterial pathogens are involved in microbial biofilm at the infection site (26). Biofilm formation in H. pylori was reported by Stark et al in 1999 (27).…”
Section: Biofilm and Helicobactermentioning
confidence: 91%
“…Recent studies have shown that many diseases associated with bacterial pathogens are involved in microbial biofilm at the infection site (26). Biofilm formation in H. pylori was reported by Stark et al in 1999 (27).…”
Section: Biofilm and Helicobactermentioning
confidence: 91%
“…The useful properties of alternative antimicrobial agents, together with advances in drug-delivery technologies, may be able to enhance and expand the medical applications of these agents (9,10,12). Combining these alternative antimicrobial agents with advanced drug-delivery systems aims to:…”
Section: Key Messagesmentioning
confidence: 99%
“…However, a disturbance to the normal ratio of microflora or an exposure of subcutaneous tissue due to trauma may result in the pathogenic invasion by these microorganisms (7). Colonisation of wounds by these opportunistic pathogens is usually polymicrobial (12). The diversity and proliferation of the pathogens is influenced by various factors including the type, depth and location of the trauma as well as the host immune system response (7).…”
Section: Microorganisms and Wound Managementmentioning
confidence: 99%
“…These biodegradable gels maintain their structure during the exchange of fluids and provide controlled release of drugs via pores in the polymer network [29,30]. When applied to wounds, hydrogels can absorb exudate while maintaining a well-oxygenated and moist environment [31,32].…”
Section: Introductionmentioning
confidence: 99%